ANALISIS PEMANFAATAN SUMBERDAYA IKAN KEMBUNG (Rastrelliger spp) DI PERAIRAN KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Siti Aminah (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Tanah Laut is a regency in South Kalimantan Province which has potential mackerel (Rastrelliger spp) resources. The objectives of the research were toestimate level utilization of in the mackerels at Tanah Laut District. Research activities which had been done included fishing gear analysis, stock analysis. The utilization level of mackerel resources had achieved 77%.